Designing a Qualitative Model of Influential Factors on Brand Hearsay in the Field of International Health Tourism - Sharifi Limaei, Delaram; Taghipourian, Mohammad Javad; Nazarpour, Soheila; Alizadeh, Ramzan (Business, Marketing, and Finance Open, 2025)
Today, an intensifying competition has emerged among various countries, especially developing Asian nations, to attract health tourists. Simultaneously, health tourism has been flourishing in developing countries. This trend underscores the necessity of focusing on brand hearsay as an effective marketing tool to attract health tourists. Accordingly, the present study aims to design a qualitative model of the influential factors affecting brand hearsay in the field of international health tourism. This research is a qualitative study that gathered qualitative data from a population of experts and senior professionals working in the Health Tourism Department of the Ministry of Health, Treatment and Medical Education, the National International Health Tourism Association, and the Office of Marketing and Development of Foreign Tourism of the Ministry of Cultural Heritage, Tourism, and Handicrafts. The sampling method employed in this study was purposive, and data collection continued until data saturation was reached, which occurred by the eleventh expert. In the qualitative phase, data analysis was conducted using thematic analysis and MAXQDA software. Based on the findings of the qualitative section of the research, the factors influencing brand hearsay in the domain of international health tourism can be categorized into four groups: brand hearsay components, drivers, inhibitors, and factors with a dual nature. Each of these categories is composed of distinct components and dimensions.